TAXATION OF FINANCIAL TECHNOLOGY AND THE TECHNOLOGY SECTOR IN INDONESIA: AN OVERVIEW OF TAX POLICY AND ITS ROLE IN SUPPORTING DIGITAL INNOVATION - Yeni Nurkhasanah; Henny Noviany; Nanang Rohman (Adisam Publisher, 2025)
The transformation of tax policy in Indonesia is crucial in responding to the rapid development of fintech and the digital economy. This article analyzes how Indonesia's tax regulations adapt to economic digitalization dynamics, highlighting government measures such as the imposition of VAT on Trade Through Electronic Systems (PMSE). Using a qualitative approach based on policy studies, this study combines interviews, policy documents, and academic literature to examine compliance, fiscal justice, and impact on innovation. The study results show that regulations are still partial and create uncertainty for business actors, while the government's main challenge is to balance state revenue with support for digital innovation. In conclusion, a more comprehensive, fair, and adaptive tax policy is needed as a fiscal instrument and catalyst for sustainable digital transformation in Indonesia.